Intrinsic Charge Transport across Phase Transitions in Hybrid Organo-Inorganic Perovskites - Yi, Hee Taek (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.